An original adaptation of photosynthesis in the marine green alga Ostreococcus - Cardol, Pierre (National Academy of Sciences, 2008)
Adaptation of photosynthesis in marine environment has been examined in two strains of the green, picoeukaryote Ostreococcus: OTH95, a surface/high-light strain, and RCC809, a deep-sea/low-light strain. Differences between the two strains include changes in the light-harvesting capacity, which is lower in OTH95, and in the photoprotection capacity, which is enhanced in OTH95. Furthermore, RCC809 has a reduced maximum rate of O(2) evolution, which is limited by its decreased photosystem I (PSI) level, a possible adaptation to Fe limitation in the open oceans. This decrease is, however, accompanied by a substantial rerouting of the electron flow to establish an H(2)O-to-H(2)O cycle, involving PSII and a potential plastid plastoquinol terminal oxidase. This pathway bypasses electron transfer through the cytochrome b(6)f complex and allows the pumping of “extra” protons into the thylakoid lumen. By promoting the generation of a large ΔpH, it facilitates ATP synthesis and nonphotochemical quenching when RCC809 cells are exposed to excess excitation energy. We propose that the diversion of electrons to oxygen downstream of PSII, but before PSI, reflects a common and compulsory strategy in marine phytoplankton to bypass the constraints imposed by light and/or nutrient limitation and allow successful colonization of the open-ocean marine environment.